Computational analysis of surface pressure distribution over a 2D wedge in the supersonic and hypersonic flow regimes - Shaikh, Javed S.; Kumar, Krishna; Pathan, Khizar A.; Khan, Sher Afghan (Tech Science Press (TSP), 2023)
The complex fluid-dynamic instabilities and shock waves occurring along the surface of a two-dimensional wedge at high values of the Mach number are studied here through the numerical solutions of the governing equations. Moreover, a regression model is implemented to determine the pressure distribution for various Mach numbers and angles of incidence. The Mach number spans the interval from 1.5 to 12. The wedge angles (θ) are from 5° to 25°. The pressure ratio (P2/P1) is reported at various locations (x/L) along the 2D wedge. The results of the numerical simulations are compared with the regression model showing good agreement.